Educational Social Media Use and Students’ Productive Language Skills: A Canonical Correlation Analysis - Saraswati; Maulana, Nanang; Santani; Ruhiat, Yayat (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
This study examines the multivariate relationship between educational social media utilization (Set X: X₁ = frequency of use, X₂ = active participation in educational activities, X₃ = creativity in creating language-related content, X₄ = content utilization for language learning) and productive language skills (Set Y: Y₁ = creative writing in digital media, Y₂ = speaking in digital media, Y₃ = debating in digital contexts, Y₄ = constructing multimodal texts) among senior secondary school students. Employing a quantitative, multivariate correlational design, 200 eleventh-grade students from SMAN 6 Tangerang Regency were selected via purposive sampling. Data were collected through validated Likert-scale questionnaires and productive language performance tasks administered online via Google Form during September 2025. Instrument reliability was established via Cronbach’s α (0.81–0.89) and McDonald’s ω (0.82–0.88), with content validity confirmed by three language education experts. Canonical Correlation Analysis (CCA) was conducted using SPSS 27, yielding four canonical functions with canonical correlations (Rc) of 0.580, 0.490, 0.258, and 0.077, respectively. Wilks’ Lambda tests confirmed that the first three canonical functions were statistically significant (overall Λ = 0.468, p < .001; Λ = 0.705, p < .001; Λ = 0.928, p = .006), while the fourth was not (Λ = 0.994, p = .280). Analysis of canonical structure coefficients revealed that Canonical Function 1 was predominantly defined by X₂ (r = 0.874) and Y₄ (r = 0.902); Function 2 by X₃ (r = −0.940) and Y₂ (r = 0.948); and Function 3 primarily by Y₃ (r = −0.983). These findings collectively indicate that students who engage more actively and creatively in educational social media activities demonstrate superior productive language competencies, particularly in multimodal composition and digital speaking, underscoring the pedagogical value of structured social media integration in secondary language education.